Mitochondria-associated endoplasmic reticulum membranes as a therapeutic target for cardiovascular diseases - Ding, Yanqiu; Liu, Nanyang; Zhang, Dawu; Guo, Lijun; Shang, Qinghua; Liu, Yicheng; Ren, Gaocan; Ma, Xiaochang (Frontiers in Pharmacology, 2024)
Cardiovascular diseases (CVDs) are currently the leading cause of death worldwide. In 2022, the CVDs contributed to 19.8 million deaths globally, accounting for one-third of all global deaths. With an aging population and changing lifestyles, CVDs pose a major threat to human health. Mitochondria-associated endoplasmic reticulum membranes (MAMs) are communication platforms between cellular organelles and regulate cellular physiological functions, including apoptosis, autophagy, and programmed necrosis. Further research has shown that MAMs play a critical role in the pathogenesis of CVDs, including myocardial ischemia and reperfusion injury, heart failure, pulmonary hypertension, and coronary atherosclerosis. This suggests thatMAMs could be an important therapeutic target for managing CVDs. The goal of this study is to summarize the protein complex of MAMs, discuss its role in the pathological mechanisms of CVDs in terms of its functions such as Ca 2+ transport, apoptotic signaling, and lipid metabolism, and suggest the possibility of MAMs as a potential therapeutic approach.